1993
DOI: 10.1590/s0103-84781993000300029
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Respiratory Syncytial Virus in Calves of Rio Grande Do Sul, Brazil

Abstract: During 20 months of the 1987-1990 period, lung tissue samples from 351 calves were obtained at a slaughterhouse. These calves were from counties nearby Porto Alegre. The direct and indirect fluorescent antibody tests (FAT) using polyclonal and monoclonal antibody conjugates were performed on frozen lung sections. Eighteen (5.13%) of the calf lung samples were positive for the Bovine Respiratory Syncytial Virus (BRSV). The BRSV was isolated from FAT positive samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
0
8
0
4
Order By: Relevance
“…Recent studies have demonstrated the presence of BRSV antibodies in numerous serum samples, as well as viral antigens in histological specimens used for the diagnosis of bovine infec- tions in the south and southeast regions of the country (6)(7)(8)(9). A serological investigation was performed with 864 serum samples from 65 different farms located in the southern Brazilian states, using serum neutralization test (SNT) and enzyme-linked immunosorbent assay (ELISA), and the clinical history was analyzed.…”
Section: Bovine Respiratory Syncytial Virus (Brsv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the presence of BRSV antibodies in numerous serum samples, as well as viral antigens in histological specimens used for the diagnosis of bovine infec- tions in the south and southeast regions of the country (6)(7)(8)(9). A serological investigation was performed with 864 serum samples from 65 different farms located in the southern Brazilian states, using serum neutralization test (SNT) and enzyme-linked immunosorbent assay (ELISA), and the clinical history was analyzed.…”
Section: Bovine Respiratory Syncytial Virus (Brsv)mentioning
confidence: 99%
“…In former studies with samples from autopsied animal tissues, the difficulty in obtaining these free and infective viruses seemed to be greater due to the time elapsed between death, autopsy and inoculation in the cell cultures (6,9). Furthermore, it is easier to obtain tissue samples from animals autopsied during the acute phase of the disease (10).…”
Section: -Brmentioning
confidence: 99%
“…Very little is known about the significance of BRSV in Brazil. Recent studies have shown BRSV antibodies in numerous serum samples and BRSV specific antigens have been detected in histological specimens of bovines submitted to veterinary diagnosis in the southern and southeastern regions of Brazil [4,9,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Em bezerros, o BRSV foi identificado desde 1967; seu primeiro isolamento foi feito na Suécia por Paccaud & Jacquier (1970). No Brasil, o primeiro registro da presença do vírus foi feita por Gonçalves et al (1993), através de imunoflorescência e cultivo celular de amostras de tecido pulmonar de bezerros, coletadas em frigoríficos na Grande Porto Alegre, RS. Campalans & Arns (1995) Fragmentos de pulmão foram colhidos em formalina a 10%, processados pelo método usual, cortados à espessura de 5µm e corados pela hematoxilina-eosina.…”
unclassified